مفهوم الاستخلاف فى القرآن الكريم، شروطه ومقاصده : دراسة أصولية - دادو، زينب أحمد (al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2006)
This study discussed the concept of Istikhlaf (vicegerency) in the Qur’ān. It identified the necessary conditions for Istikhlaf and the basic factors which would allow an individual to achieve it in real life. The study also explained the purpose of Istikhlaf and its ultimate objectives, as well as elucidating the method which Allah has sent to assist Man in discharging his duty as a vicegerent on earth according to what is revealed in the Qur’an. Furthermore, the study dealt with the concept of Istikhlaf among some exegesists and presented the views of some Muslim thinkers on the topic. It is important to appreciate the scholars’ significance since their contributions are key in restoring the dynamism that Islamic thought had lost. This was achieved by correcting the misconception of Istikhlaf among the public. The only way to achieve Istikhlaf is by strengthening faith, and revisiting the relationship between a servant ('abd) and his Lord, which has a strong correlation with ‘Aqidah. The study relied on historical analysis to trace the concept of Istikhlaf throughout its various stages of development. It also adopted a deductive method for analyzing, comparing ideas and deriving their meanings. The study concluded that the concept of Istikhlaf is a Qur’anic expression of human civilization. Consequently, it is necessary to correct the misconception of Istikhlaf among the public in order to build a civilization based on Divine scheme that is suitable to humankind.